Mechanical fusion coated lithium ion battery negative electrode material and preparation method thereof
The nano-scale conductive passivation layer is coated in the lithium-ion battery through mechanical fusion coating method, which solves the performance problems caused by volume expansion and reaction with the electrolyte in the lithium-ion battery, and achieves higher stability and conductivity, reducing process costs.
Patent Information
- Application Number
- CN202411843017.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Silicon-based materials in lithium-ion batteries have rapid attenuation of battery capacity and poor circulation performance due to volume expansion and reaction with electrolyte in lithium-ion batteries, and the high-temperature coating process is complex and costly.
Using a mechanical fusion coating method, by covering the nano-scale conductive passivation layer on the surface of the silicon-based material, the specific steps include using mechanical fusion method to grind overmolding under a protective atmosphere, controlling the distance between the rolling hammer and the tank wall and the distance between the scraper and the tank wall to ensure effective coating.
It improves the stability and conductivity of silicon-based materials, reduces the internal resistance of the battery, avoids the adverse effects of high temperature on silicon materials, and reduces process costs.
Smart Images

Figure CN119627082A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a mechanically fused and coated lithium ion battery negative electrode material and a preparation method thereof. Background Art
[0002] Silicon-based materials have an extremely high theoretical specific capacity (3579mAh / g), which is nearly 10 times that of graphite negative electrodes, and are considered to be the most promising negative electrode materials for next-generation lithium-ion batteries. However, silicon-based materials have a huge volume expansion effect during the charge and discharge process, and are prone to pulverization and failure; at the same time, the exposed silicon material reacts with the electrolyte to form a new solid electrolyte membrane (SEI), resulting in rapid battery capacity decay, poor cycle performance, and large first irreversible capacity loss.
[0003] Carbon-coated amorphous / nano-silicon is an effective strategy to solve the above-mentioned problems of silicon-based materials and realize the large-scale application of silicon materials. Coating carbon materials on the surface of silicon-based materials can effectively alleviate the volume expansion of silicon-based materials during the charging and discharging process, inhibit the excessive growth of SEI, and improve the cycle stability of materials. In addition, carbon materials also have good electrical conductivity and can build a continuous conductive network on the surface of silicon-based materials, reduce the internal resistance of the battery, and thus improve battery performance. Commonly used carbon coating methods and technologies include vapor deposition, hydrothermal method, pyrolysis method, etc., as shown in Table 1: Table 1 Comparison of carbon coating technology routes.
[0004] In Table 1, the advantages and disadvantages of several commonly used carbon coating technologies are summarized from five aspects: the temperature required for the carbon coating method, the impurity phase, and the order, uniformity and integrity of the carbon after coating, and the equipment requirements. Currently, commercial carbon coating needs to be achieved at a high temperature above 800°C. However, when the temperature reaches above 600°C, amorphous silicon will crystallize, and nano-silicon will also recrystallize and grow, ultimately reducing the stability of lithium storage cycles. In addition to the impact of high temperature on silicon-based materials, the carbon coating process is relatively complicated. At the same time, by-products may be produced during the pyrolysis process, such as low-value pyrolysis gas, tar, etc. The treatment of these by-products increases the process cost and may also cause environmental problems. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a mechanically fused coated lithium ion battery negative electrode material, which has the characteristics of high stability, good processability and excellent electrochemical performance.
[0006] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a mechanically fused and coated negative electrode material for a lithium-ion battery. The negative electrode material comprises a silicon-based material with a core structure, and a nano-conductive passivation layer is coated on the outer layer of the silicon-based material. The silicon-based material is a micron-sized powder, and the coating material is a nano-sized titanium powder. The ratio of the particle size of the silicon-based material to the particle size of the conductive material, i.e., R / r≥100; the ratio of the number of conductive material particles to the number of silicon-based material particles is greater than 80,000:1 and less than 120,000:1. This is because the nano-conductive passivation material at least completely coats the silicon-based core material. Assuming that the projected area of n nano-conductive spheres is equal to the specific surface area of 1 silicon-based core material sphere, i.e. nr 2 ≥4 R 2 , and n≥40000. For the silicon-based core material to be completely covered without any gaps, at least two layers of nanospheres (n≥80000) are required; more than three layers (n≤120000) are not recommended, because the coating material is an inactive substance, and adding too much will reduce the capacity of the electrode material. The silicon-based material and the coating material are ground and coated by mechanical fusion under protective atmosphere conditions.
[0007] Furthermore, the control parameters of the mechanical fusion method are: the distance between the rolling hammer and the tank wall is 0.5-10mm; the distance between the scraper and the tank wall is 0.2-5mm. If the distance between the rolling hammer and the tank wall is too small or too large, the extrusion effect between the silicon-based materials cannot be achieved, and the coating effect is not ideal; if the distance between the scraper and the tube wall is too small, there is a risk of introducing impurities from the tube wall, and if the distance is too large, the conductive material cannot be scraped off.
[0008] Furthermore, the silicon-based material is one or more of pure silicon, silicon alloy, and silicon monoxide.
[0009] Furthermore, the coating material is a metal nitride or boride, including but not limited to one or more of Li3N, TiN, AlN, TaN, TiB2 and ZrB2, and its particle size r ranges from 5 to 50 nm. These materials have excellent electrical conductivity, acid and alkali resistance, and can resist corrosion from electrolytes.
[0010] Furthermore, the protective atmosphere is one or more of argon, nitrogen, helium and neon.
[0011] Furthermore, the particle size range of the silicon-based material is 1-30 μm, which is convenient for subsequent coating processing as a negative electrode material.
[0012] Furthermore, the ratio of the particle size of the silicon-based material to the particle size of the conductive material, i.e., R / r ≥ 100; the ratio of the number of conductive material particles to the number of silicon-based material particles is 80,000:1-120,000:1. This is because the nano-conductive material at least completely covers the silicon-based core material. Assuming that the projected area of n nano-conductive spheres is equal to the specific surface area of 1 silicon-based core sphere, that is nr 2 ≥4 R 2 , and n≥40000. For the silicon-based core material to be completely covered without gaps, at least two layers of nanospheres (n≥80000) are required; more than three layers (n≤120000) are not recommended, because the conductive material is an inactive substance, and adding too much will reduce the capacity of the electrode material. Specifically, in order to ensure the operability of the particle number ratio, it is generally achieved by controlling the mass ratio, and the specific mass ratio is calculated in combination with the particle number ratio and volume.
[0013] Furthermore, the distance between the rolling hammer and the tank wall is regulated according to the particle size of the conductive material and the silicon-based material, and the distance between the scraper and the tank wall is regulated according to the particle size of the conductive material.
[0014] Another aspect of the present invention is to protect the negative electrode material of lithium ion battery, and the negative electrode material is prepared by the above preparation method.
[0015] The present invention discloses a mechanically fused coated lithium ion battery negative electrode material and a preparation method thereof, which has the following beneficial effects: The lithium ion battery negative electrode material of the present invention effectively solves the problem of high temperature coating causing the base silicon grain size to grow, consolidates the stability of the silicon-based material, and also further enhances the conductivity of the material, while also avoiding the corrosion of HF generated by the side reaction of the electrolyte to the silicon material.
[0016] The lithium ion battery silicon-based negative electrode material prepared by the method of the present invention has good electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The morphology changes before and after coating (a and b are before coating, and ef is after coating).
[0018] Figure 2 For Si 75 Ti 20 Voltage-specific capacity comparison before and after Co5 coating TiN. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0020] The invention discloses a method for preparing a mechanically fused and coated lithium-ion battery negative electrode material. The negative electrode material comprises a silicon-based material with a core structure and a conductive nano passivation layer coated outside the silicon-based material. The silicon-based material is a micron-sized powder, and the coating material is a nano-sized nitride or boride. The silicon-based material and the coating material are ground and coated by mechanical fusion under protective atmosphere conditions.
[0021] Furthermore, the control parameters of the mechanical fusion method are: the distance between the rolling hammer and the tank wall is 0.5-10 mm; the distance between the scraper and the tank wall is 0.2-5 mm.
[0022] Furthermore, the silicon-based material is one or more of pure silicon, silicon alloy, and silicon monoxide.
[0023] Furthermore, the nano-conductive coating material is one or more of Li3N, TiN, AlN, TaN, TiB2 and ZrB2, and its particle size r ranges from 5 to 50 nm.
[0024] Furthermore, the protective atmosphere is one or more of argon, nitrogen, helium and neon.
[0025] Furthermore, the particle size R of the silicon-based material ranges from 1 to 30 μm.
[0026] Furthermore, the ratio of the particle size of the silicon-based material to the particle size of the coating material is R / r≥100; and the ratio of the number of coating material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0027] Furthermore, the silicon-based material is spheroidized before mechanical fusion. The spheroidization method is that the high-speed rotating centrifugal force evenly throws the silicon-based powder material onto the tank wall, the mechanical hammer squeezes the material, and the rear scraper scrapes the material off the tank wall. This method spheroidizes the silicon-based material and makes the surface of the material smoother, which is conducive to subsequent mechanical fusion.
[0028] Another aspect of the present invention is to protect the negative electrode material of lithium ion battery, and the negative electrode material is prepared by the above preparation method.
[0029] During the mechanical fusion process, the changes in various parameters will directly affect the performance of the material, which is specifically reflected in: At the material property level, choosing compatible materials for bonding can improve bonding strength and stability. The shape of the particles (such as spherical, flake or irregular) will affect the packing density and contact conditions, thereby affecting the bonding effect.
[0030] At the environmental conditions level, humidity and atmosphere: The humidity and atmosphere of the environment may affect the chemical reaction and bonding effect of the materials, especially in the processing of certain sensitive materials.
[0031] Example 1 The present embodiment relates to a method for preparing a mechanically fused and coated lithium-ion battery negative electrode material, wherein the negative electrode material comprises a silicon-based material with a core structure and a conductive nano-passivation layer coated outside the silicon-based material. The silicon-based material is a micron-sized powder, and the coating material is a nano-sized nitride. The silicon-based material and the coating material are ground and coated by mechanical fusion under protective atmosphere conditions.
[0032] In this embodiment, the control parameters of the mechanical fusion method are: the distance between the rolling hammer and the tank wall is 10 mm; the distance between the scraper and the tank wall is 3 mm. The protective atmosphere is argon.
[0033] In this embodiment, in terms of material type selection, the silicon-based material is pure silicon, and the particle size R of the silicon-based material ranges from 1 to 30 μm; the nano-conductive coating material is Li3N, and its particle size r ranges from 5 to 50 nm; the ratio of the particle size of the silicon-based material to the particle size of the coating material R / r≥100; the ratio of the number of coating material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0034] In this embodiment, the silicon-based material is spheroidized before mechanical fusion. The spheroidization method is that the high-speed rotating centrifugal force evenly throws the silicon-based powder material onto the tank wall, the mechanical hammer squeezes the material, and the rear scraper scrapes the material off the tank wall. This method spheroidizes the silicon-based material and makes the material surface smoother, which is conducive to subsequent mechanical fusion.
[0035] Example 2 The present embodiment relates to a method for preparing a mechanically fused and coated lithium-ion battery negative electrode material, wherein the negative electrode material comprises a silicon-based material with a core structure and a conductive nano-passivation layer coated outside the silicon-based material. The silicon-based material is a micron-sized powder, and the coating material is a nano-sized nitride. The silicon-based material and the coating material are ground and coated by mechanical fusion under protective atmosphere conditions.
[0036] In this embodiment, the control parameters of the mechanical fusion method are: the distance between the rolling hammer and the tank wall is 5 mm; the distance between the scraper and the tank wall is 0.2 mm. The protective atmosphere is nitrogen and helium.
[0037] In this embodiment, in terms of material type selection, the silicon-based material is a silicon alloy, and the particle size R of the silicon-based material is in the range of 1-30 μm; the nano-conductive coating material is TiN and AlN, and its particle size r is in the range of 5-50 nm; the ratio of the particle size of the silicon-based material to the particle size of the coating material is R / r≥100; the ratio of the number of coating material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0038] In this embodiment, the silicon-based material is spheroidized before mechanical fusion. The spheroidization method is that the high-speed rotating centrifugal force evenly throws the silicon-based powder material onto the tank wall, the mechanical hammer squeezes the material, and the rear scraper scrapes the material off the tank wall. This method spheroidizes the silicon-based material and makes the material surface smoother, which is conducive to subsequent mechanical fusion.
[0039] Example 3 The present embodiment relates to a method for preparing a mechanically fused and coated lithium-ion battery negative electrode material, wherein the negative electrode material comprises a silicon-based material with a core structure and a conductive nano-passivation layer coated outside the silicon-based material. The silicon-based material is a micron-sized powder, and the coating material is a nano-sized nitride. The silicon-based material and the coating material are ground and coated by mechanical fusion under protective atmosphere conditions.
[0040] In this embodiment, the control parameters of the mechanical fusion method are: the distance between the rolling hammer and the tank wall is 0.5 mm; the distance between the scraper and the tank wall is 5 mm. The protective atmosphere is helium and neon.
[0041] In this embodiment, in terms of material type selection, the silicon-based material is silicon monoxide, and the particle size R of the silicon-based material ranges from 1 to 30 μm; the nano-conductive coating materials are AlN and TaN, and their particle size r ranges from 5 to 50 nm; the ratio of the particle size of the silicon-based material to the particle size of the coating material R / r≥100; the ratio of the number of coating material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0042] In this embodiment, the silicon-based material is spheroidized before mechanical fusion. The spheroidization method is that the high-speed rotating centrifugal force evenly throws the silicon-based powder material onto the tank wall, the mechanical hammer squeezes the material, and the rear scraper scrapes the material off the tank wall. This method spheroidizes the silicon-based material and makes the material surface smoother, which is conducive to subsequent mechanical fusion.
[0043] Example 4 The present embodiment relates to a method for preparing a mechanically fused and coated lithium-ion battery negative electrode material, wherein the negative electrode material comprises a silicon-based material with a core structure and a conductive nano-passivation layer coated outside the silicon-based material. The silicon-based material is a micron-sized powder, and the coating material is a nano-sized boride. The silicon-based material and the coating material are ground and coated by mechanical fusion under protective atmosphere conditions.
[0044] In this embodiment, the control parameters of the mechanical fusion method are: the distance between the rolling hammer and the tank wall is 30 mm; the distance between the scraper and the tank wall is 4 mm. The protective atmosphere is argon gas and neon gas.
[0045] In this embodiment, in terms of material type selection, the silicon-based material is silicon alloy and silicon monoxide, and the particle size R of the silicon-based material ranges from 1 to 30 μm; the nano-conductive coating material is TiB2 and ZrB2, and its particle size r ranges from 5 to 50 nm; the ratio of the particle size of the silicon-based material to the particle size of the coating material R / r≥100; the ratio of the number of coating material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0046] In this embodiment, the silicon-based material is spheroidized before mechanical fusion. The spheroidization method is that the high-speed rotating centrifugal force evenly throws the silicon-based powder material onto the tank wall, the mechanical hammer squeezes the material, and the rear scraper scrapes the material off the tank wall. This method spheroidizes the silicon-based material and makes the material surface smoother, which is conducive to subsequent mechanical fusion.
[0047] Example 5 The present embodiment relates to a method for preparing a mechanically fused and coated lithium-ion battery negative electrode material, wherein the negative electrode material comprises a silicon-based material with a core structure and a conductive nano-passivation layer coated outside the silicon-based material. The silicon-based material is a micron-sized powder, and the coating material is a nano-sized boride. The silicon-based material and the coating material are ground and coated by mechanical fusion under protective atmosphere conditions.
[0048] In this embodiment, the control parameters of the mechanical fusion method are: the distance between the rolling hammer and the tank wall is 8 mm; the distance between the scraper and the tank wall is 2 mm. The protective atmosphere is neon gas.
[0049] In this embodiment, in terms of material type selection, the silicon-based material is pure silicon, silicon alloy, and silicon oxide, and the particle size R of the silicon-based material ranges from 1 to 30 μm; the nano-conductive coating material is ZrB2, and its particle size r ranges from 5 to 50 nm; the ratio of the particle size of the silicon-based material to the particle size of the coating material R / r≥100; the ratio of the number of coating material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0050] In this embodiment, the silicon-based material is spheroidized before mechanical fusion. The spheroidization method is that the high-speed rotating centrifugal force evenly throws the silicon-based powder material onto the tank wall, the mechanical hammer squeezes the material, and the rear scraper scrapes the material off the tank wall. This method spheroidizes the silicon-based material and makes the material surface smoother, which is conducive to subsequent mechanical fusion.
[0051] Application Example 1 This embodiment relates to a lithium-ion battery negative electrode material coated with mechanical fusion, and the preparation process is as follows: 10 Si with a D50 of 25 μm 75 Ti 20The Co5 alloy material is coated with 4wt% TiN powder with a size of 20 nm using a mechanical solid phase fusion machine. The mechanical hammer spacing is 5 mm, the scraper spacing is 0.5 mm, the coating time is 4 h, and the ratio of the number of coated material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0052] Application Example 2 This embodiment relates to a mechanical fusion coated lithium ion battery negative electrode material, and the preparation process is as follows: Si with a D50 of 25 μm 75 Ti 20 The Co5 alloy material is added with 4wt% Li3N powder with a size of 20nm and coated with a mechanical solid phase fusion machine. The mechanical hammer spacing is 5mm, the scraper spacing is 0.5mm, the coating time is 4h, and the ratio of the number of coated material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0053] Application Example 3 This embodiment relates to a mechanical fusion coated lithium ion battery negative electrode material, and the preparation process is as follows: Si with a D50 of 25 μm 75 Ti 20 The Co5 alloy material is added with 4wt% TaN powder with a size of 20nm and coated with a mechanical solid phase fusion machine. The mechanical hammer spacing is 5mm, the scraper spacing is 0.5mm, the coating time is 4h, and the ratio of the number of coated material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0054] Application Example 4 This embodiment relates to a mechanical fusion coated lithium ion battery negative electrode material, and the preparation process is as follows: Si with a D50 of 25 μm 75 Ti 20 The Co5 alloy material is added with 4wt% TiB2 powder with a size of 20nm and coated with a mechanical solid phase fusion machine. The mechanical hammer spacing is 5mm, the scraper spacing is 0.5mm, the coating time is 4h, and the ratio of the number of coated material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0055] Application Example 5 This embodiment relates to a mechanical fusion coated lithium ion battery negative electrode material, and the preparation process is as follows: Si with a D50 of 25 μm 75 Ti 20 The Co5 alloy material is added with 4wt% ZrB2 powder with a size of 20nm and coated with a mechanical solid phase fusion machine. The mechanical hammer spacing is 5mm, the scraper spacing is 0.5mm, the coating time is 4h, and the ratio of the number of coated material particles to the number of silicon-based material particles is 80000:1-120000:1.
[0056] Comparative Example 1 Compared with the above-mentioned application example 1, the main difference between comparative example 1 is that there is no nano passivation layer coated.
[0057] In order to effectively evaluate the technical effect of the present invention, the electrochemical performance of lithium ion batteries was tested using Examples 1-5 and the comparative example. The test results are shown in Table 2.
[0058] Table 2 Comparison of electrochemical performance of Examples 1-5 and Comparative Example 1 like Figure 1 As shown, (a, b, c) are SEM images of comparative example 1, where it can be observed that the alloy particles are spherical and the spherical surface is relatively smooth. (d, e, f) are SEM images of Example 1, where it can be observed that the size of the coated particles is slightly larger than the material before coating, and a layer of covering material is clearly visible on the surface of the particles, which can be preliminarily determined that the conductive material is coated on the silicon-based spherical particles. Figure (g) is the distribution of the N element, such as the distribution of N on the particle surface is relatively uniform. Figure (h) is a SEM image of the cross section of Example 1, where the TiN layer on the surface of the spherical particles can be observed.
[0059] like Figure 2 As shown, the blank part before the previous curve is deducted before the comparison of its reversible capacity. Both Comparative Example 1 and Example 1 show the lithiation / delithiation characteristic curve of amorphous silicon, which further verifies that the silicon material is not affected by temperature during the coating process. Crystallization and growth. It can be observed that the first lithiation potential of Example 1 is increased from 0.10 V to 0.22 V, indicating that a better conductive network is constructed after TiN coating, reducing the generation of polarization.
[0060] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A method for preparing a mechanically fused coated lithium-ion battery negative electrode material, the negative electrode material comprising a silicon-based material with a core structure and a conductive nano passivation layer coated outside the silicon-based material, characterized in that: The silicon-based material is a micron-sized powder, the coating material is a nano-sized nitride or boride, and the silicon-based material and the coating material are ground and coated by mechanical fusion under protective atmosphere conditions.
2. The method for preparing a mechanically fused coated lithium ion battery negative electrode material according to claim 1, characterized in that: The control parameters of the mechanical fusion method are: the distance between the rolling hammer and the tank wall is 0.5-10 mm; the distance between the scraper and the tank wall is 0.2-5 mm.
3. The method for preparing a mechanically fused coated lithium ion battery negative electrode material according to claim 2, characterized in that: The silicon-based material is one or more of pure silicon, silicon alloy, and silicon monoxide.
4. The method for preparing a negative electrode material for a lithium-ion battery coated by mechanical fusion according to claim 3, characterized in that: The nano-conductive coating material is one or more of Li3N, TiN, AlN, TaN, TiB2 and ZrB2, and its particle size r ranges from 5 to 50 nm.
5. The method for preparing a negative electrode material for a lithium-ion battery coated by mechanical fusion according to claim 4, characterized in that: The protective atmosphere is one or more of argon, nitrogen, helium and neon.
6. The method for preparing a mechanically fused coated lithium ion battery negative electrode material according to claim 5, characterized in that: The particle size R of the silicon-based material ranges from 1 to 30 μm.
7. The method for preparing a negative electrode material for a lithium-ion battery coated by mechanical fusion according to claim 6, characterized in that: The ratio of the particle size of the silicon-based material to the particle size of the coating material is R / r≥100; the ratio of the number of coating material particles to the number of silicon-based material particles is 80000:1-120000:
1.
8. The method for preparing a mechanically fused coated lithium ion battery negative electrode material according to claim 7, characterized in that: The silicon-based material is spheroidized before mechanical fusion. The spheroidization method is that the high-speed rotating centrifugal force evenly throws the silicon-based powder material onto the tank wall, the mechanical hammer squeezes the material, and the rear scraper scrapes the material off the tank wall. This method spheroidizes the silicon-based material and makes the material surface smoother, which is conducive to subsequent mechanical fusion.
9. A negative electrode material for a lithium ion battery, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Negative electrode material for lithium-ion battery and preparation method and application of negative electrode material
CN106531980A
Mechanical co-coating method for modified composite material containing silicon-base material, the modified composite material, and lithium ion battery
CN109411713A
Ceramic phase silicon-nitrogen layer coated silicon negative electrode material, preparation method and application of ceramic phase silicon-nitrogen layer coated silicon negative electrode material
CN114420912A
Nonaqueous electrolyte secondary cell and negative electrode of the same
JP2001325950A
Negative-electrode active substance, method for manufacturing same, and lithium-ion secondary cell
WO2014207921A1